Association of human myxovirus resistance protein A with severity of COVID-19 - Lehtinen, Otto (My University, 2023)
This study aims to indentify if there is a correlation between blood human myxovirus resistance protein A (MxA) level and severity of disease in hospitalized COVID-19 patients. MxA is an intracellular GTPase, which inhibits production of new viruses at early stage of their life cycle. MxA is detectable within hours and has a half-life of 2.3 days, which makes it useable as an indicator of acute virus infection. All 304 patients admitted for COVID-19 in Turku University Hospital until 30th of April 2021 were included. MxA was measured from peripheral blood samples in 268 cases. Patients were divided in groups based on their level of MxA on admission. Baseline characteristics and severity of disease on admission based on clinical parameters and inflammatory biomarker levels were studied in each group. Severity of disease during hospitalization was determined by the applied level of respiratory support, by the usage of corticosteroids and by the duration of hospitalization. Higher MxA levels on admission were associated with more severe disease. Adjusted Odds Ratios for any respiratory support were 9.92 (95%CI 2.11 – 46.58; p=0.004) in patients with MxA between 400 μg/L and 799 μg/L (p=0.004) and 20.08 (95%CI 4.51 – 89.44; p<0.001) in patients with MxA 800 μg/L in comparison with patients with initial MxA <400 μg/L. The usage of corticosteroids was significantly higher in the high-MxA group (77%) in comparison with the intermediate-MxA group (62%, p=0.013) and low-MxA group (47%, p<0.001). Higher initial levels of MxA were associated with more severe COVID-19. MxA may be a helpful additional biomarker predicting the severity of the disease.
Keywords: COVID-19, SARS-CoV-2, human myxovirus resistance protein A, MxA